Records Of The Colony Of New Plymouth In New England 230 (1861) - (:unkn) unknown (My University, 1671)
Laws of Plymouth Colony (1671). Whereas several persons have been greatly endangered by setting of guns, it is enacted by the Court and the authority thereof that none shall sett any guns except in enclosures and that the gun be sufficiently enclosed so as it be secure from hurting man or beast and that he that setteth the gun do give warning or notice thereof to all the neighbors on penalty of paying a fine of five pounds to the use of the Colony for every default.
Keywords: TRAP GUNS